The origins of pain in diverticular disease: peripheral or central? - Smith, Janette Kate (2013)
This study was designed to identify the processes which underlie pain in symptomatic diverticular disease (SDD). Our hypothesis was that a spectrum of both peripheral and central pathologies were involved, with those that had a more peripheral problem having abdominal symptoms only while those with multiple symptoms throughout the body, having an altered central pain processing. The first study examining the brain response to cutaneous pain using functional magnetic resonance imaging (fMRI) has supported this hypothesis. Although a statistically significant difference in sensory pain threshold was not demonstrated between the groups, fMRI imaging has shown greater emotional processing during pain and reduced anticipatory inhibitory responses in the high somatising symptomatic diverticular disease (HSDD) groups. However this is not as clear cut as we had anticipated which may be due to subject selection and demonstrate a spectrum of mixed peripheral and central changes as well as those with only peripheral or central components.